Effect of washing on the storage stability of Selaroides leptolepsis and Aristichthys nobilis surimi - Siah, Watt Moey; Yu, Swee Yean; Abdul Rahman, Russly; Mat Hashim, Dzulkifly (Asian Fisheries Society, 1998)
This study was undertaken to determine the effects of washing and storage on the quality of Selaroides leptolepis and Aristichthys nobilis surimi kept at -20ºC for 24 weeks. Surimi was prepared from unwashed once-washed and twice-washed minces. Analyses conducted include changes in texture profile, expressible moisture, color, elasticity, moisture content, pH, salt-soluble protein, trimethylamine, total volatile basic nitrogen and thiobarbituric acid. Results showed that twice-washed surimi of both species were generally more stable than once-washed and unwashed surimi. They storage quality in terms of texture, color, elasticity, moisture content, pH and salt soluble protein values for all samples showed significant decreases during storage. There were increases in expressible moisture, trimethylamine, total volatile basic nitrogen and thiobarbituric acid.